Reframing Trauma: The Potential of Narrative Therapy in the Rehabilitation of Gender-Based Violence Survivors - Kamran, Tafiya Erum; Faisal, Seyreen; Faisal, Romaan (Journal of the Pakistan Medical Association, 2025)
Respected Editor, We are writing this letter to put forward a severely underutilized trauma intervention referred to as Narrative Therapy (NT). This Therapy acts as a compelling conduit for reframing an individual’s experience, allowing them to have more positive outlooks regarding their trauma and dispelling prior notions. [1] In narrative therapy, individuals shape their life experiences in a way that allows them to find meaning. This coaxes individuals to break free from the shackles of trauma, and truly focus on perseverance in the face of immense hardship and struggle. [1] We believe that NT can be an innovative approach to managing the trauma associated with gender-based violence (GBV). Although there are limited acute means of support for victims of GBV, there is almost no avenue for the chronic rehabilitation of these individuals. [1] Gender Based Violence is perpetuated by deeply ingrained gender inequality. It has persisted as an undeniable contributor to human rights violations in multiple social frameworks.[2] Pakistani society is entrenched in a culture of oppression, possession, and objectification towards women. There is a direct link between GBV and the health status of women, encompassing physical injuries, permanent disabilities, psychological disorders, suicide, sexually transmitted diseases, unwanted pregnancies, female feticide, unsafe abortions, and death. [2] Physical ailments though apparent, it is the unrecognized mental health illnesses directly caused by GBV that remain widely unacknowledged. Despite its global prevalence, serious consequences, and afflictions to women, GBV has not yet been declared a public health issue. [3] Patients suffering from depression were able to have more positive and hopeful outlooks on life with the intervention of NT. [4] The success and satisfaction of patients with PTSD after NT intervention has established it as an alternative treatment with boundless potential for managing such conditions. [5] We feel that narrative therapy or storytelling could be similarly useful in the rehabilitation of GBV survivors. We believe that given the opportunity to express themselves in their own words, GBV victims would feel empowered as they articulate their stories on their terms thus facilitating their healing.